THE CHALLENGE OF EVASION IN HIGHER EDUCATION COURSES IN THE MODALITY OF EaD. - Pedrosa, Rafael Alves (2019)
The evasion in distance courses is one of the main obstacles institutions. In this scenario, it includes the upper courses that have been offered by the Virtual University of the State of São Paulo - UNIVESP. This study had as objective to analyze the causes of evasion in superior courses offered in the distance modality. In order to do so, 100 students evaded these courses completed, so online, social profile, behavior and attitudes of the student in relation to distance learning courses are covered in the questionnaire. The results indicate that a significant portion of the escaped performed other tasks concurrent with the course; even expose that escaped the good part of the interviewees presented difficulties of iteration with the platforms used in the learning process, as well as mapping of the social profile of these individuals. As conclusions are: the fact that the EaD is a reality and as points this study with bias of sharp growth in the coming years, but also indicates the need for changes in processes and in relationship with students enabling not only their access to EaD but its effective utilization and permanence in the courses and institutions, be they public or private, who offer this type of education, and also the need of further studies that may give continuity to mapping and solutions pointing to the inclusion or exclusion of items that increase the reliability of EaD and minimize the factors identified as the cause of the circumvention.